2017
DOI: 10.1016/j.neuroimage.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cortical structural plasticity in humans after a day of waking and sleep deprivation

Abstract: Sleep is an evolutionarily conserved process required for human health and functioning. Insufficient sleep causes impairments across cognitive domains, and sleep deprivation can have rapid antidepressive effects in mood disorders. However, the neurobiological effects of waking and sleep are not well understood. Recently, animal studies indicated that waking and sleep are associated with substantial cortical structural plasticity. Here, we hypothesized that structural plasticity can be observed after a day of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 81 publications
7
45
1
Order By: Relevance
“…Therefore, the impairment of behavioral performance after SD could be actually detected by using neuroimaging methods. Also, this evidence from functional neuroimaging was further proved in a structural imaging study which observed a thinned cortical thickness precuneus and posterior cingulate cortex after SD [48].…”
Section: Working Memory and Alff Changes After Sdmentioning
confidence: 76%
“…Therefore, the impairment of behavioral performance after SD could be actually detected by using neuroimaging methods. Also, this evidence from functional neuroimaging was further proved in a structural imaging study which observed a thinned cortical thickness precuneus and posterior cingulate cortex after SD [48].…”
Section: Working Memory and Alff Changes After Sdmentioning
confidence: 76%
“…Notwithstanding the impairment in neuropsychological tests targeting cortical functions, possibly due to saturation and altered signal/noise ratio associated with acute imbalance of circadian synaptic homeostasis, these experiments consistently suggest that one night of SD increases cortical excitability and synaptic strength in healthy humans. Similarly, there is new evidence for neuroplasticity of such an extent as to be associated with an increase of prefrontal cortical brain volumes detected in structural MRI after SD in healthy humans (Elvsashagen et al., ).…”
Section: What Are the Perspectives?mentioning
confidence: 97%
“…Forty right-handed, healthy, adult male volunteers were included. Functional and structural MRI data from overlapping samples were previously investigated [34][35][36] . We included males only, in order to exclude potential variability due to hormonal cycles.…”
Section: Descriptive Characteristics and Study Designmentioning
confidence: 99%